Impression formation via #foodporn: Effects of posting gender-stereotyped food pictures on instagram profiles. (1st April 2020) - Cavazza, Nicoletta; Graziani, Anna Rita; Guidetti, Margherita
Abstract: Previous studies suggested that food may have gender connotations and plays an important role in impression formation. Since sharing food images through social networks is becoming more and more common, the aim of the present study was to examine whether such images influence observers' judgements of a target. Specifically, we hypothesised that posting images of gender-stereotyped dishes would affect impression formation as a function of their congruence with the sex of the profile owner. In a 2 × 3 study, we varied the sex of the owner of a fictitious Instagram profile, and the image-set composition (masculine dishes vs feminine dishes vs neutral images). Subsequently, we measured the perceived femininity/masculinity, gender-stereotyped traits, and the desire to interact with the profile owner. Results confirmed that food pictures can communicate a profile owner's characteristics, showing that posting masculine dishes dampened women's femininity and the attribution of feminine traits to the target, irrespective of gender, and indirectly reduced participants' intention to meet both targets through the lower attribution of feminine traits (i.e., communion). Moreover, posting gender-congruent food images promoted the congruent gendered impression in observers (i.e., femininity for the woman and masculinity for the man) and in turn increased the desire to interact with him/her. These findings contribute to the understanding of the socio-psychological functions at the basis of sharing one's own eating/cooking experiences on social networks, showing that this behavior has an informational role for observers.